2020
DOI: 10.1088/2051-672x/ab58b8
|View full text |Cite
|
Sign up to set email alerts
|

Study on the rolling friction and wear properties of surface densified powder metallurgy Fe-2Cu-0.6C material

Abstract: Rolling friction and wear behaviours of a surface densified Fe-2Cu-0.6C powder metallurgy material were investigated. Results indicated that friction coefficient and wear were significantly decreased after rolling. Wear rate tended to be steady as the rolling cycle increases. Under light load, wear was caused by delamination and ploughing. Delamination crack initiated on material surface. Under heavy load, wear was caused by delamination and pits. Cracks initiated at the surface and subsurface. However, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These defects were formed by adhesive wear, and also related to the chemical reaction between rolling oil and active metal surface. The detailed magnification showed that copper here was fragmented, which further defined that areas with casting defects were more likely to stick [25]. The corresponding EDS analysis is shown in figures 5(f)-(h).…”
Section: Microstructure Of Rolled Stripsmentioning
confidence: 90%
“…These defects were formed by adhesive wear, and also related to the chemical reaction between rolling oil and active metal surface. The detailed magnification showed that copper here was fragmented, which further defined that areas with casting defects were more likely to stick [25]. The corresponding EDS analysis is shown in figures 5(f)-(h).…”
Section: Microstructure Of Rolled Stripsmentioning
confidence: 90%
“…They concluded that there was a reduction in friction and rolling resistance. In the low load application, the plowing and delaminations were observed whereas, at high load pits and cracks were initiated [140]. Guo et al have studied the fabrication and tribological behavior of iron-based porous bearings.…”
Section: Tribology In Bearingsmentioning
confidence: 99%
“…The high-hardness surface produced by machining forces the crack initiation site closer to the surface during wear, and the residual compressive stress inhibits the rate of crack expansion, considered as the main reason for the enhanced wear resistance. Liu et al [13,14] employed SBP on the Fe-2Cu-0.6C powder metallurgical material to produce simultaneous fine crystallization and densification of the surface layer, obtaining a high-quality surface layer with a surface hardness of 330 HV0.01 and a depth of 335 μm in the densification layer. The rolling wear test showed that SBP changes the wear mechanism, in which the crack initiation position in the machined sample is closer to the surface, and the crack length is shorter, reducing the wear amount by 50%.…”
Section: Introductionmentioning
confidence: 99%